Behavioral characteristic of deaf and hard of hearing students and students of typical development in the educational process - Mijatović, Svetlana; Radovanović, Vesna (Specijalna edukacija i rehabilitacija, 2020)
Introducion. In addition to family, school has an irreplaceable role in the development and behavior of children, because it it is a place of  social interaction between students, students and teachers, as well as other adults, which differs significantly from the interaction within immediate and extended family. Objectives. This research aimed to determine and describe the behavior of deaf and hard of hearing children and children of typical development in different school situations. Methods. The sample consisted of 52 lower elementary school students, 7 to 11 years of age, divided into two groups –  group A with 26 deaf and hard of hearing students, and group B with 26 students of typical development. With regard to gender,  the sample consisted of 34 (65.4%) male students and 18 (34.6%) female students. The Questionnaire for assessing the behavior of younger school childrenwas used in this research. Results. The results of the research showed that there were statistically significant differences between deaf and hard of hearing students and students of typical development in class behavior: with regard to the place where they sat (χ2 = 19.57, df = 8, rc = .52, p = .01), and attention during lessons (χ2 = 16.70, df = 8, rc = .49, p = .03); during recess: with regard to playing  (χ2 = 20.13, df = 8, rc = .52, p = .01); or with regard to authority: when they addressed teachers (χ2 = 7.06, df = 8, rc = .49, p = .03), received orders (χ2 = 27.58, df = 8, rc = .58, p = .001) and praise (χ2 = 27.84, df = 8, rc = .59, p = .001). Age, gender, school success, and the type of amplification in deaf and hard of hearing students did not proove to be factors that significantly affected student behavior. Conclusion. More extensive research on personal (degree of hearing loss, language competence), family (parent-child dyad) and social factors (inclusive and non-inclusive education), would explain some of the unknowns related to the behavior of deaf and hard of hearing students.
Keywords: deaf and hard of hearing students; primary school age; behavior